Evidence-Based Evaluation Technique to Assess Augmentation Mammaplasty Results: A Simple Method to Objectively Analyze Mammary Symmetry and Position. (November 2014) - Mazzocchi, Marco; Dessy, Luca Andrea; Fallico, Nefer; Alfano, Carmine; Scuderi, Nicolò
Background: Despite the great variety of mammaplasty techniques, outcome assessment remains a challenging issue. Objectives: The authors devised an objective method to evaluate mammary symmetry based on statistical analysis of objective manual breast measurements and validated the method by applying it to results of a randomized controlled trial on the correction of breast asymmetry. Methods: Sixty consecutive patients with hypoplastic breasts and small-volume asymmetry were enrolled in the study and randomly assigned to 1 of 2 groups. One group received a fixed-volume implant in 1 breast and an adjustable-volume implant in the other. The other group received 2 fixed-volume implants of different sizes. The differences in specific breast and chest measurements, obtained before surgery and during follow-up, were analyzed statistically with the Wilcoxon signed rank test. Results: Correction of the asymmetry resulted in the reduction of the differences between left and right values for each specific breast measurement. Placement of an adjustable implant on 1 side yielded better symmetry than placement of 2 fixed-volume prostheses of different sizes. Patient and physician satisfaction was high for both groups. Conclusions: This objective analysis of clinical parameters enables comparing results for different patients in large clinical trials and for the same patient at different follow-up periods. Level of Evidence: 3